Exendin-4, a glucagon-like peptide 1 receptor agonist, protects cholangiocytes from apoptosis. Issue 7 (1st October 2008) - Marzioni, M; Alpini, G; Saccomanno, S; Candelaresi, C; Venter, J; Rychlicki, C; Fava, G; Francis, H; Trozzi, L; Benedetti, A
Abstract : Background and aims: Progression of chronic cholestatic disorders towards ductopenia results from the dysregulation of cholangiocyte survival, with cell death by apoptosis prevailing over compensatory proliferation. Currently, no therapy is available to sustain cholangiocyte survival in the course of those disorders. It was recently shown that cholangiocytes express the glucagon-like peptide-1 receptor (GLP-1R); its activation results in enhanced proliferative reaction to cholestasis. The GLP-1R selective agonist exendin-4 sustains pancreatic β cell proliferation and prevents cell death by apoptosis. Exendin-4 is now employed in humans as a novel therapy for diabetes. The aim of the present study was to verify whether exendin-4 is effective in preventing cholangiocyte apoptosis. Methods: In vitro, tests were carried out to determine if exendin-4 is able to prevent apoptosis of cholangiocytes isolated from normal rats induced by glycochenodeoxycholic acid (GCDCA); in vivo, animals subjected to 1 week of bile duct ligation and to a single intraperitoneal injection of CCl4 were treated with exendin-4 for 3 days. Results: Exendin-4 prevented GCDCA-induced Bax mitochondrial translocation, cytochrome c release and an increase in caspase 3 activity. Phosphatidylinositol 3-kinase, but not cAMP/protein kinase A or Ca 2+ /calmodulin-dependent protein kinase inhibitors, neutralised the effects of exendin-4. In vivo, exendin-4 administration prevented the increase in TUNEL (terminal deoxynucleotidyl transferase-mediated triphosphate end-labelling)-positive cholangiocytes and the loss of bile ducts observed in bile duct-ligated rats treated with CCl4 . Conclusion: Exendin-4 prevents cholangiocyte apoptosis both in vitro and in vivo; such an effect is due to the ability of exendin-4 to counteract the activation of the mitochondrial pathway of apoptosis. These findings support the hypothesis that exendin-4 may be effective in slowing down the progression of cholangiopathies to ductopenia.